KEMAMPUAN INTERAKSI SOSIAL SISWA MELALUI PENDEKATAN PEMBELAJARAN SOSIAL EMOSIONAL PADA PEMBELAJARAN IPAS SISWA KELAS VI SDN GUE GAJAH ACEH BESAR - Maulida, Afrilia; Safiah, Intan; Tursinawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the importance of elementary school students’ social interaction skills, which still show variations, particularly in Science and Social Studies (IPAS) learning. Low participation, lack of empathy, and suboptimal cooperation among students indicate the need for a learning approach that focuses not only on cognitive aspects but also on social-emotional aspects. This study aimed to describe students’ social interaction skills through a social-emotional learning approach and to identify the factors that support and hinder the process. This study employed a qualitative approach with a descriptive design. The research subjects were teachers and sixth-grade students at SD Negeri Gue Gajah Aceh Besar. Data were collected through observation and interviews. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results showed that students’ social interaction skills through a social-emotional learning approach were categorized as very good, with an average percentage of 84.1%. The students’ social interaction skills in the aspects of conversation reached 89.9%, mutual understanding 82.5%, cooperation 83.7%, openness 82.1%, empathy 80%, providing support 80%, positive attitude 83.7%, and equality 92.5%. Although overall the results were categorized as very good, the aspects of empathy and providing support were relatively lower compared to the other aspects. Supporting factors of students’ social interaction included teacher role modeling, peer influence, teacher guidance and motivation, the desire to be accepted in groups, and caring attitudes. Meanwhile, inhibiting factors included students’ lack of self-confidence, the dominance of certain students in discussions, imitation of negative behavior, and a lack of mutual respect.